2016
DOI: 10.1021/acs.jafc.5b05892
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Novel Maltose-Forming α-Amylase from Lactobacillus plantarum subsp. plantarum ST-III

Abstract: A novel maltose (G2)-forming α-amylase from Lactobacillus plantarum subsp. plantarum ST-III was expressed in Escherichia coli and characterized. Analysis of conserved amino acid sequence alignments showed that L. plantarum maltose-producing α-amylase (LpMA) belongs to glycoside hydrolase family 13. The recombinant enzyme (LpMA) was a novel G2-producing α-amylase. The properties of purified LpMA were investigated following enzyme purification. LpMA exhibited optimal activity at 30 °C and pH 3.0. It produced onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Amy2 from L. plantarum subsp. plantarum ST-III has been previously characterized and its maltose-forming α-amylase activity described [7]. Amy2 from this strain has an amino acid sequence identical to Lp_0179 (Amy2) from L. plantarum WCFS1 (data not shown).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Amy2 from L. plantarum subsp. plantarum ST-III has been previously characterized and its maltose-forming α-amylase activity described [7]. Amy2 from this strain has an amino acid sequence identical to Lp_0179 (Amy2) from L. plantarum WCFS1 (data not shown).…”
Section: Resultsmentioning
confidence: 95%
“…This result confirmed that both enzymes hydrolysed α-1,4-glucosidic bonds. However, the activity of Lp_0179 (LpMA) on p NP-α- d -maltopentaoside was previously analysed reporting that Lp_0179 hydrolyzed the α-1,4-glucosidic bonds of p NP-α- d -maltopentaoside, resulting in production of maltose and p NP-α- d -maltotriose [7]. This result could be in agreement with the results reported in our study, as Lp_0179 was unable to liberate p NP (detected colorimetrically) but able to hydrolyze one internal α-1,4-glucosidic bond to liberate p NP-α- d -maltotriose and maltose (detected by HPAEC and thin layer chromatography) [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that L. plantarum has amylolytic activity up to 20 U/ml and cellulolytic activity up to 12 U/ml after 18 h of fermentation at a steady temperature of 37°C during cassava fermentation [27]. Enzyme amylase activity from L. plantarum also has been observed by several researchers [29][30][31]. Cellulolytic property of microorganism is essential for breaking down the cell wall of cassava roots, resulting in improving physical properties of a mocaf product.…”
Section: Fermentationmentioning
confidence: 91%
“…Although D. fristingensis is a psychrotolerant yeast having an optimal growth temperature at 15°C, its secreted α-glucosidase exhibit the best activity at 37-40°C having its K m value on soluble starch of 1.3 g/L. This K m value is in the range typical for microbial α-amylases and glucoamylases described to be best active at 40-50°C, but is lower than that for the enzymes with optimal activity above 60°C [13,[48][49][50]. In relation to thermal inactivation of the α-glucosidase from D. fristingensis, its decimal reduction time at 30°C, 40°C and 50°C was 12.5, 10.5 and 7 h, respectively.…”
Section: Thermal Inactivation Of D Fristingensis α-Glucosidasementioning
confidence: 97%